PEMBERIAN AROMATERAPI LAVENDER TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF PADA IBU BERSALIN PRIMIPARA - Siti Rohimah; Siti Rohimah (Universitas Fort De Kock, 2021)
The first stage of labor pain is the feeling of pain and discomfort experienced by the mother from the beginning of labor until the cervix is maximally dilated (10 cm). The purpose of this study was to determine the effect of giving lavender aromatherapy on the reduction of labor pain intensity at the I-active phase in primiparous women. The research design used was quasi-experimental with a non-equivalent control group design. The sample in this research was 20 primiparous women who were divided into two groups, 10 respondents were given lavender aromatherapy and 10 respondents were given endorphin massage. The results showed that the average pain intensity before giving lavender aromatherapy was 6.70 and after giving lavender aromatherapy the average pain intensity was 4.90. The average pain intensity before giving endorphin massage was 7.30 and after giving endorphin massage the average pain intensity was 5.60. The results of statistical tests using the Independent T-test obtained a p-value = 0.31, which means that there was no significant effect of pain intensity between mothers who are given lavender aromatherapy with endorphin massage. It is hoped that health workers can apply therapy of nonpharmacological lavender aromatherapy to reduce the intensity of labor pain as obstetric care for childbirth.